2000
DOI: 10.1021/bi000690j
|View full text |Cite
|
Sign up to set email alerts
|

Domains I and III of the Human Copper Chaperone for Superoxide Dismutase Interact via a Cysteine-Bridged Dicopper(I) Cluster

Abstract: Copper binding to the human copper chaperone for superoxide dismutase (hCCS) has been investigated by X-ray absorption spectroscopy. Stoichiometry measurements on the dialyzed, as-isolated protein indicated that up to 3.5 Cu ions bound per hCCS molecule. Reduction with either sodium dithionite or dithiothreitol decreased the copper binding ratio to 2 coppers per hCCS monomer. Analysis of the as-isolated EXAFS data indicated coordination of Cu by a mixture of S and N backscatterers, suggestive of heterogeneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
58
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 42 publications
10
58
0
Order By: Relevance
“…3 S at 2.24 Å and 1 Cu at 2.70 Å) has been observed in yeast Cox11 for which Cys residues are involved in copper binding (15). The distance of 2.7 Å is in accordance with Cu-Cu distances observed in doubly bridging sulfur complexes, which range from 2.7 to 3.0 Å, whereas the Cu-Cu distances in singly bridged sulfur clusters are around 3.3 Å (45,46). Similar EXAFS data were also found for Cu(I)-CopZ samples, indicating a common copper binding motif (47).…”
Section: Interaction With Copper: Xas and Nmr Characterization-to Chasupporting
confidence: 73%
See 1 more Smart Citation
“…3 S at 2.24 Å and 1 Cu at 2.70 Å) has been observed in yeast Cox11 for which Cys residues are involved in copper binding (15). The distance of 2.7 Å is in accordance with Cu-Cu distances observed in doubly bridging sulfur complexes, which range from 2.7 to 3.0 Å, whereas the Cu-Cu distances in singly bridged sulfur clusters are around 3.3 Å (45,46). Similar EXAFS data were also found for Cu(I)-CopZ samples, indicating a common copper binding motif (47).…”
Section: Interaction With Copper: Xas and Nmr Characterization-to Chasupporting
confidence: 73%
“…4). Indeed, the observed Cu-Cu distance of 2.7 Å is typical of doubly bridging sulfur complexes (56,57) and was found in other copper(I) chaperones with similar rearrangements (45,58). The N-terminal Cys-9, which is located far from the CFCF binding site and in an unstructured region only five/four residues of the inner membrane, would not be involved in copper binding but rather could be involved in an intermolecular disulfide bond with the corresponding cysteine of the other monomeric unit (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…A number of studies have shown that the Cu(I) coordination number and͞or geometry are correlated with the intensity of this transition (38,39). The height of the 1s-4p transition present in the edge of the Cu(I)-CopC spectrum suggests 3-or 4-coordination for Cu(I) (39,41).…”
Section: Xas Spectra Analysismentioning
confidence: 99%
“…Whereas the mechanism by which SOD1 acquires Zn(II) is not fully understood, several aspects of the copper insertion by the copper chaperone for SOD1 (CCS) are well established (7)(8)(9)(10)(11)(12). More recently, Furukawa et al (13) have shown that the intrasubunit disulfide bond is correctly introduced in yeast SOD1 by the copper-bound form of yeast CCS.…”
mentioning
confidence: 99%